Β‐Crystal formation in isotactic polypropylene due to rapid heat cycle molding. (21st May 2015) - Li, Jiquan; Zhou, Hangchao; Xu, Fuyu; Jiang, Shaofei; Zheng, Wei
Abstract : Performance of the rapid heat cycle‐molded products is highly correlated to its multilayer structure and crystal form in the multilayers. In this study, isotactic polypropylene was introduced in molding experiments, multi‐sites sampling was carried out, and β ‐crystal contents together with multilayer structure were characterized by scanning electron microscopy and X‐ray diffraction. It is shown that the distribution of β ‐crystal is significantly relevant to the multilayer structure. Meanwhile, a higher mold‐heating temperature would benefit the formation of β ‐crystal, the content of which is mainly dependent on mold temperature and filling distance. Copyright © 2015 John Wiley & Sons, Ltd.